Age at Immigration Matters for Labor Market Integration: The Swedish Example - Björn Anders Gustafsson; Hanna Mac Innes; Torun Österberg (Institute of Labor Economics (IZA), 2016)
This paper analyses how age at immigration to Sweden and getting a first foothold in the labor market is related. We estimate hazard rate models using registry data on all persons who arrived in each of the years 1990, 1994, 1998, and 2002. The results show that the number of years taken to get a foothold in the Swedish labor market increases rapidly by age among immigrants from middle- and low-income countries aged 40 +. Most individuals who are born in middle- or low-income countries who immigrate after age 50 never get a foothold in the Swedish labor market.
Keywords: C41; J15; J61; 330; immigrants; Sweden; age; labor market